Digital Culture and Intercultural Citizenship in Peru: A Conceptual Cartography - Turpo-Gebera, Osbaldo; Alanoca-Gutiérrez, Rebeca; Valle-Castro, Gina Maribel; Ballón-Bahamondes , Roberto Daniel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The digital society is reconfiguring the relationships between digital culture and intercultural citizenship in Peru. To understand these connections, it is important to examine thesis reports presented in Peruvian universities. Conceptual mapping is used as a research method, allowing for the identification of emerging thematic connections. The results demonstrate a growing interest in research on digital culture and intercultural citizenship in Peru, as well as the interconnections and gaps that highlight national inequalities. Essentially, the need for public policies that promote digital culture, and an active and participatory intercultural citizenship online is revealed.